Preterm Birth Alters the Maturation of the GABAergic System in the Human Prefrontal Cortex - Lacaille, Helene; Vacher, Claire-Marie; Penn, Anna A. (Frontiers in Molecular Neuroscience, 2022)
Developmental changes in GABAergic and glutamatergic systems during frontal lobe development have been hypothesized to play a key role in neurodevelopmental disorders seen in children born very preterm or low birth weight, but the associated cellular changes have not yet been identified. Here we studied the molecular development of the GABAergic system specifically in the dorsolateral prefrontal cortex, a region that that has been implicated in neurodevelopmental and psychiatric disorders. The maturation state of the GABAergic system in this region was assessed in human post-mortem brain samples, from term infants ranging in age from 0 to 8 months (n=17 male, 9 female). Gene expression was measured for 47 GABAergic genes and used to calculate a maturation index. This maturation index was significantly more dynamic in male than female infants. To evaluate the impact of premature birth on the GABAergic system development, samples from one-month-old term (n=9 male, 4 female) and one-month corrected-age (n=8 male, 6 female) very preterm infants, were compared using the same gene list and methodology. The maturation index for the GABAergic system was significantly lower (–50% p<0.05) in male preterm infants, with major alterations in genes linked to GABAergic function in astrocytes, suggesting astrocytic GABAergic developmental changes as a new cellular mechanism underlying preterm brain injury.